Kecemasan di Masa Pandemi Covid-19 Ditinjau dari Gender - Nur Irmayanti; Ardianti Agustin; Mohammad Wasil (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
This study aims to determine what factors affect anxiety during the Covid-19 pandemic in terms of gender. While this research method uses a literature review method used to collect library data in the form of articles of information sources both from national and international by using database searches through mass media (online news), books, google scholars and elsevier. The results show that women are twice as likely to experience psychiatric disorders related to stress and anxiety compared to men, in this case due to several demographic factors (health, social, gender, age and economic status).